(untitled) (Journal of Partial Differential Equations, 2019)
In this paper, we consider an elliptic equation with exponential nonlinearities and singular term. By constructing the corresponding variational framework, and using a Singular Trudinger-Moser inequality due to Li, Mountain-pass theorem and the Ekeland’s variational principle, we get a nontrivial positive weak solution.